1989
DOI: 10.1172/jci113993
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the generation of superoxide anions in hematoporphyrin derivative-mediated cutaneous photosensitization. Activation of the xanthine oxidase pathway.

Abstract: Prior studies, both in vitro and in vivo, have suggested that cutaneous porphyrin photosensitization requires the generation of superoxide anion 2O-) and various other reactive oxygen metabolites. No unifying concept has emerged, however, that unequivocally demonstrates the source of generation of these species. Since xanthine oxidase is known to generate *02 in reperfused ischemic tissue and in certain inflammatory disorders, we attempted to assess its role in porphyrin photosensitization. C3H mice were rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…In addition to our finding that intravenous SOD administration immediately after photodynamic light treatment decreases the cure rate of PDT-treated mouse FsaR and EMT6 tumours (Korbelik et al, 2000), Athar et al (1989) have shown that the effect of PDT on mouse skin can be augmented by an SOD inhibitor and diminished by an SOD mimic. Using ESR spectroscopy, the superoxide production was also documented in PDT-treated tissues (Athar et al, 1988) and in photoirradiated aqueous photosensitiser liposomal preparations (Hajdur et al, 1997a, b).…”
Section: Donovansupporting
confidence: 49%
“…In addition to our finding that intravenous SOD administration immediately after photodynamic light treatment decreases the cure rate of PDT-treated mouse FsaR and EMT6 tumours (Korbelik et al, 2000), Athar et al (1989) have shown that the effect of PDT on mouse skin can be augmented by an SOD inhibitor and diminished by an SOD mimic. Using ESR spectroscopy, the superoxide production was also documented in PDT-treated tissues (Athar et al, 1988) and in photoirradiated aqueous photosensitiser liposomal preparations (Hajdur et al, 1997a, b).…”
Section: Donovansupporting
confidence: 49%
“…34,35 Physicochemical properties of porphyrinsPorphyrin distribution in tissues depends on its physicochemical properties. URO and Copro are hydrophilic and accumulate majorly in the lower epidermis and upper dermis; on the other hand, protoporphyrin (Proto) has greater affinity with lipid membranes (endothelial cell and lisosome membrane).…”
Section: Figurementioning
confidence: 99%
“…Taken together, these data would confirm an important role for singlet oxygen in the photosensitization process. However, other oxygen species, such as superoxide and hydrogen peroxide, may contribute as well (Maillard et al, 1980, Ben Hur et al, 1985Athar et al, 1989;Kimel et al, 1989). To establish how important any of these species might be in photosensitization damage to the integrins, cellular adhesion was measured after photosensitization in the presence of various compounds which can modulate the effects of reactive oxygen species.…”
Section: Effect Of Quenchers and D 2 O On Photosensitized Damage To Cmentioning
confidence: 99%